The Relationship between UPF (Ultra Processed Food) Consumption, Stress Levels, Quality of Life with CKD (Chronic Kidney Disease) Grade - Ari Lestari; Tri Rahayu Hikmah Kurniatin; Yulidian Nurpratiwi; Retno Anggraeni Puspita Sari (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Chronic Kidney Disease (CKD) is one of the top 5 most common inpatient diseases at Sentra Medika Cisalak Hospital in 2024, with a high prevalence of 3.49%. This high disease burden indicates the urgency of identifying lifestyle and psychological factors, such as UPF consumption and stress, that influence the disease grade. This study aims to analyze the relationship between UPF consumption, stress levels, and quality of life in Chronic Kidney Disease patients. This research method uses a quantitative research type with a cross-sectional approach. The population is all Chronic Kidney Disease patients from grades 1-5 with a total of 121 respondents, and a sample of 93 respondents using a random sampling technique. The instruments used are FFQ (Food Frequency Questionnaire), PSS (Perceived Stress Scale), and WHOQOL (World Health Organization Quality of Life) questionnaires. The results of univariate analysis showed that the majority of respondents were men aged 40-60 years with a college education, where most of them consumed excessive UPF and had low stress levels, but their quality of life was assessed as poor. The results of the bivariate analysis using the Chi-Square Test with a p-value <0.05 indicate a relationship between UPF consumption (p-value 0.016) and stress levels (p-value 0.044) with Chronic Kidney Disease patients. However, no relationship was found between quality of life and CKD grade patients at Sentra Medika Cisalak Hospital (p-value 0,061). Suggestions for further research should consider studies that last for a longer period and include biochemical data to obtain more comprehensive analysis results.